INFLUÊNCIA DE FATORES REGIONAIS NA DIVERSIDADE E COMPOSIÇÃO DE PEIXES NO ALTO RIO PARANÁ, MATO GROSSO DO SUL - CAMPOS, Débora Gomes; FERREIRA, Fabiane Silva; PINHO, Henrique Ledo Lopes; SÚAREZ, Yzel Rondon (ANAIS DO ENIC, 2024)
-